EFFECTS OF PROTON PUMP INHIBITORS ON HEPATIC ENCEPHALOPATHY IN PATIENTS WITH CIRRHOSIS - Yarmukhamedova Saodat Khabibovna; Bekmuradova Makhsuda Salkhidinovna (Scholar Express Journals, 2022)
In our study we determined whether proton pump inhibitor (PPI) use in patients with hepatic encephalopathy predisposes to more severe hepatic encephalopathy with cirrhosis according to West Haven criteria. We found that long-term PPI use in patients with cirrhosis accompanied by gastroduodenal pathology was associated with significantly higher mean West-Haven criteria for hepatic encephalopathy compared with patients who did not use proton pump inhibitors. Our study also showed that cirrhotic patients with clear signs of hepatic encephalopathy receiving PPIs have longer hospital stays, with increased morbidity and mortality during their hospital stay
Keywords: Hepatic Encephalopathy; Cirrhosis; Proton Pump Inhibitors; Portal Hypertension